The electronic and optoelectronic properties of Al/hydroxymethyl functionalized Zn(II)Pc/p-Si photonic device - Al-Sehemi, Abdullah G. G.; Ocakoglu, Kasim; Ince, Mine; Karabulut, Abdulkerim; Tataroglu, A.; Dere, Aysegul; Yakuphanoğlu, Fahrettin (Springer, 2024)
In this study, the effects of illumination on the electronic and optoelectronic properties of Al/hydroxymethyl functionalized Zn(II)Pc/p-Si/Al photonic device have been investigated under dark and various lighting conditions. The diode's electronic parameters have been extracted from the current-voltage characteristics. It is observed that the dark current value increases when the light is illuminated on the device, and thus, the photocurrent is formed, and this result has shown that the studied device exhibits a photoconductive behavior. The photoresponse properties of the fabricated device have been examined by transient photocurrent measurements under 100 mW/cm(2) illumination, and they have also been analyzed using photocapacitance and photoconductivity measurements at different frequencies (100 kHz, 500 kHz, and 1 MHz). However, the capacitance data that may occur between the poles of the produced device have also been investigated, and it is thought that the device can also be developed as a capacitor. These results confirm that the hydroxymethyl functionalized Zn(II)Pc and p-silicon semiconductor-based device can be used particularly in electro-optic and photonic applications.
Keywords: Photodiode; Photoresponse; Illumination effect; Transient measurements; Frequency effect